Developing Students’ Competences in the Era of Technology: Experience of Integrating Writing in a Content Course at Christian Bilingual University of Congo - Mashauri, Mumbere Malonga; Pato, Malobi; Makuru, Lotsove (Journal of Education and Practice, 2024)
Purpose: The purpose of this study was double: 1) To describe the aspects of technology that were involved in the process of integrating writing in the teaching of a discipline. 2) To identify some students’ skills/competences that began to improve thanks to writing integration in the teaching of a content course. Methodology: Qualitative practices were used in data collection processes. Data were collected through participatory method, semi-structured interview, informal conversation and tutorial sessions. In order to determine the sample for our study, we used the type of sampling called “Purpose Sampling”. The strategy used for this type of sampling was “Homogenous Sampling” in which the researchers identified individuals because of their membership in a group that has a well-defined characteristic. Based on this strategy, the subgroup consisted of students who took the course with the researcher in the first semester and in the first quarter of the second semester (139 in intensive English, 16 in Media Concepts, 2 in Method of University Work, 1 in Business English, and 23 in Initiation to Scientific Research) and the students whom the researcher supervised their thesis. The participants, thus, in this study were 44. Content and thematic analysis were used in the process of data analysis. Findings: Four results have been revealed throughout this study: 1) The integration of writing into the course has begun to improve students’ language proficiency. 2) The integration of writing into the course has begun to improve students’ cognitive proficiency. 3) Incorporating writing in the content courses began to enhance collaborative competence between students. 4) Incorporating writing into the course begun to develop students’ proficiency in using ICT tools. Unique Contribution to Theory, Practice and Policy: Developing students’ competences in content as well as in language should adopt the integrated approach in which teachers incorporate technology related activities as well as writing activities. Regarding the benefits that technology offers in the process of content and language development, and owing to the fact that incorporating writing contribute to students’ language proficiency, content acquisition, cognitive development, etc. researchers recommend the use of the integrated approach in which content, language, technology and writing are integrated in order to have a holistically trained student.